Studies on H2-Assisted Liquefied Petroleum Gas Reduction of NO over Ag/Al2O3 Catalyst - Pratichi Singh; Deepak Yadav; Pooja Thakur; Jitendra Pandey; Ram Prasad (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
Hydrocarbon-Selective catalytic reduction (HC-SCR) is one of the potential methods to remove NOx emissions from diesel engine, lean burn petrol engines and natural gas engines exhaust. Ag/Al2O3 is a good catalyst for HC-SCR of NOx under lean-burn conditions. Further, addition of small amount of H2 is effective for enhancing HC-SCR activity. This effect is unique to silver and to specific Ag/support combinations, namely, Ag/γ-Al2O3. Various HC reductants, such as: octane, decane, dodecane and propane, have been reported in the literatures. Only a single study on LPG as a reductant over Cu-ZSM catalyst was reported. There was no work reported on H2 assisted LPG over Ag/Al2O3 catalyst. Thus, this gap in the literature is filled with the present investigation of NO reduction over 2 wt.% Ag/Al2O3 catalyst using LPG reductant. The fresh and used catalyst was characterized by various techniques like low temperature N2-adsorption, XRD, XPS and SEM. There was practically no change in the characteristics of the fresh and used catalyst. Two different reductants of CO and LPG were compared for SCR of NO over the catalyst without and with H2-assisted. The experiments were performed in a fixed bed tubular flow reactor under the following conditions: 100mg catalyst; 0.13% NO, 2.5% LPG/CO, 1% H2, 10% O2, rest Ar; total flow rate 60 mL/min; temperature ambient 400 oC and pressure 1 atm. Around 100% conversion of NO was achieved using LPG reductant. Light off temperature of NO reduction significantly reduced by H2assisted LPG reductant. The maximum conversion of NO with CO was limited to 35.15% at temperature of 224 oC and above. Whereas, 97.79 % NO conversion was achieved at 365 oC with LPG reductant. While, the maximum conversions with H2-LPG and H2-CO reductants were 100 and 99.46% at 117 and 220 oC, respectively. Therefore, H2-LPG-SCR of NOx over 2 wt.% Ag/Al2O3 catalyst system can be used to get 100% reduction at low temperature.